Providing Authentic Assessments for SMPN 03 Lebong and MAN Rejang Lebong Teachers in Support of the Merdeka Curriculum Implementation - Euis Nursa'adah; Aceng Ruyani; Bhakti Karyadi; Elsi Adelia Fitri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
All schools, both middle and high school levels, are preparing to implement the Merdeka Curriculum in the following year. Learning innovations in the Merdeka Curriculum must be accompanied by the ability to assess learning outcomes and processes appropriately. Assessments are no longer based on paper and pencil tests but must authentically assess student skills. Through authentic assessment as an alternative assessment, students are accustomed to carrying out work according to job demands, where tasks are designed to follow real-world replication. Authentic assessment has the potential to improve learning for students ready to work in the real world. The ability to design authentic assessments is provided in this activity through the I-CARE design at SMPN 03 Lebong and MAN Rejang Lebong. This activity was attended by 30 teachers from both schools. The results show that the majority of teachers can distinguish between diagnostic, formative, and summative assessment functions, besides being able to understand the types of authentic assessment and being able to design authentic assessments to support student-centered learning by the character of the Merdeka Curriculum.